Encontros e desencontros: um olhar sobre a velhice em uma Instituição de Longa Permanência para Idosos - Raquel de Oliveira Barreto (2012)
The aim of this paper is to understand how old people who live in a nursing home subjectively experience old age, and also to analyze how this experience of the subjects is felt by the Institution (Long Term Care Institution) and how this influences its practice. Even though the growth of the elderly population is a global reality and its frequently used to justify researches about the theme, our interest is specifically on the position which is provided to the old people in a contemporary society. In this regard, besides numerical questions, the fact is that the elderly is still considered a minority, without political and social participation. In order to understand the dynamic and values which establishes todays society we based on the concept of narcissistic society, developed by Lasch (1983). From this perspective, we discuss how old age is incompatible with beauty ideals and youthfulness valued in todays society, as well as fear related to death can be explained by the narcissistic desire of immortality. We based on the understanding that the old is considered a stranger whom we dont want to establish reciprocal ties because he reminds us, every moment, of our own aging process and inevitable death. Taking into account our especial interest in the reality of the elderly in Long Term Care Institutions, we try to understand the scenario of the Brazilian nursing homes and to reflect about the meanings and the role in the society. The psychoanalysis was used in this research as a theoretical frame able to offer elements for a social analysis. We chose a critical-theoretical positioning; we directed our search to reveal and discuss the conditions of oppression which permeates reality, contributing not only to the reflection of the existence of inequalities but also to long for the possibility of change. Based on this theoretical layout we conducted a study in the qualitative case in the Lar dos Idosos, a nursing home located in the town of Divinopolis, Minas Gerais. Many techniques in data collection were used to allow us to reach a depth level required in the research proposal: the immersion in the subjectivities. In this sense, we chose to run a participant observation during a period of six months, and also the interviews of professionals from the nursing home and the recollection of life stories. For the analysis, there was a comprehensive interpretation in the data collected, aspiring not only the speech explicit content but also the silenced one. The results appoints to an existence of a distortion between the institutional look and the subjects which results in a loss for the Institution in reference to reaching their objectives but especially for the subjects who constantly suffer with the restrain of their autonomy and with the careless aspects which affects subjectively. With the possibilities to lessen the irregularities, questions such as the need to prepare professionals who are dealing with the elderly, and the need that the aging becomes socially re-modified are discussed.